Implantable CMOS Biomedical Devices - Toshihiko Noda; Takashi Tokuda; Jun Ohta; Kiyotaka Sasagawa (Sensors, 2009)
The results of recent research on our implantable CMOS biomedical devices are reviewed. Topics include retinal prosthesis devices and deep-brain implantation devices for small animals. Fundamental device structures and characteristics as well as in vivo experiments are presented.